2021
DOI: 10.21776/ub.jkb.2021.031.04.4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Benign Prostatic Hyperplasia (BPH) Patients Undergoing Transurethral Resection of the Prostate (TURP)

Abstract: <p class="EnglishAbstract">Benign prostatic hyperplasia (BPH) is one of the most common diseases affecting the elderly, and Transurethral Resection of the Prostate (TURP) is a gold standard surgical procedure in BPH patients. Although the TURP rate is high, the publication of TURP profile data in Indonesia is still limited. This study aimed at determining the characteristics of BPH patients who underwent TURP at Saiful Anwar General Hospital. This study is a descriptive study by collecting data of 162 BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
3
0
2
Order By: Relevance
“…Research (Husni, 2016) states that for patients with benign prostatic hyperplasia, the most common type of therapy is TURP as many as 64 people (76.2%). This research is also supported by research (Roar, 2015), showing that patients with benign prostatic hyperplasia are most often given TURP therapy, and this often occurs in the 73-77-year-old age group (24.6%). Transurethral Resection of Prostate (TURP) is a therapy for benign prostatic hyperplasia using a minimum intervention operative method.…”
Section: Discussionsupporting
confidence: 53%
“…Research (Husni, 2016) states that for patients with benign prostatic hyperplasia, the most common type of therapy is TURP as many as 64 people (76.2%). This research is also supported by research (Roar, 2015), showing that patients with benign prostatic hyperplasia are most often given TURP therapy, and this often occurs in the 73-77-year-old age group (24.6%). Transurethral Resection of Prostate (TURP) is a therapy for benign prostatic hyperplasia using a minimum intervention operative method.…”
Section: Discussionsupporting
confidence: 53%
“…A previous study also concluded on the sixth to the twelfth day, the continuous monotherapy tamsulosin administration has an upregulation impact ( 20 , 21 ). On the first day, the prostate's smooth muscle cells are less contractile; however, by the sixth to the twelfth day, they are more so ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 89%
“…This explains the possibility of a tolerance that requires further research. A previous study also concluded on the sixth to the twelfth day, the continuous monotherapy tamsulosin administration has an upregulation impact ( 18 , 19 ). On the first day, the prostate’s smooth muscle cells are less contractile; however, by the sixth to the twelfth day, they are more so ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 91%